Association of Bacterial Conjunctivitis in Optical Lenses Users - Maqbool Ahmed Jamali, Nisar Ahmed Khan, Nisar Ahmed Jandan, Ashfaque Ahmed Abbasi, Ateeq-Ur-Rehman, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find the association of bacterial conjunctivitis in optical lenses users. Study Design: Observational based cross-sectional study Place and Duration of Study: Department of Ophthalmology, People Medical College Hospital Nawabshah from 1st April 2021 to 30th September 2021. Methodology: Thirty five patients who walked in the out-door department were enrolled. Those patients who had clinical symptoms positive for bacterial conjunctivitis and were using optical lenses were included in the study. Demographic information and information regarding their hygienic practices and usage of optical lenses was entered in a well-structured proforma. Sterile cotton-swabs were used for collecting samples from the lenses. Post 24 hours in broth at 37°C the samples were placed in blood agar for culturing at 37°C for two days.Kirby–Bauer disc diffusion method was then performed for isolation of bacterial cultures using susceptibility of bacteria towards various antibiotics. Results: There 48.75% females which was higher than males (34.28%). Dryness appeared to be the most common symptoms followed by redness and itchy eyes. The culturing and bacterial isolation method for BC showed that micrococci were presented in majority of the cases (n=29) which was followed by diphtheroid in 18 patients. Conclusion: Strong association of bacterial conjunctivitis was found in relation with optical lenses users.